Internet-Interventionen in der Psychotherapie - Berger, Thomas; Bur, Oliver; Krieger, Tobias (PPmP - Psychotherapie · Psychosomatik · Medizinische Psychologie, 2019)
Die Erforschung und Anwendung internetbasierter psychosozialer Interventionen hat in den letzten Jahren rapide zugenommen. Das neue Behandlungsformat bietet viele Chancen, weckt aber auch Skepsis und Bedenken. Dieser Beitrag gibt einen Überblick über verschiedene Formen von Internet-Interventionen, neuere Entwicklungen und den aktuellen Stand in Forschung und Praxis.Over the past few years, research and application of internet-based psychotherapeutic interventions has grown rapidly. This kind of new therapeutic format offers a variety of chances for treating patients with psychotherapeutic disorders, but also arouses skepticism and concerns. This overview focuses on different forms of internet-based psychotherapeutic interventions, reflects the current state of research, and points out new areas of development as well as its implementation in daily practice.
Keywords: Internet-Interventionen; Online-Psychotherapie; Selbsthilfe; Blended Psychotherapie